2023
DOI: 10.1128/spectrum.00409-23
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Tissue Metabonomics Combined with 16S rRNA Gene Sequencing To Analyze the Changes of Gut Microbiota in Mice with Endometritis and the Intervention Effect of Tau Interferon

Abstract: The change in intestinal flora has been the focus of many disease studies in recent years, but the pathogenetic effect of interferon on endometritis is still unclear. The results of this study showed that IFN-τ alleviated the damage in mouse endometritis induced by E. coli and improved the endometrial tissue barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Studies have shown that the relative abundance of Enterorhabdus in intestinal microbiota is related to glycolipid metabolism ( Huang et al., 2023 ; Lahtinen et al., 2023 ), and Enterorhabdus abundance in PCOS mice is positively correlated with T level and blood glucose ( Li Y. et al., 2023 ). Interferon may affect the expression level of important metabolites in uterine tissue by reducing the abundance of Enterorhabdus in intestinal microbiota, thus alleviating the injury of endometritis in mice ( Xue et al., 2023 ). Lactobacillus has a protective effect on the ovaries, restoring luteinizing hormone, follicle-stimulating hormone, and testosterone levels, upregating short-chain fatty acid levels, and improving intestinal microbiota disorders ( He et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the relative abundance of Enterorhabdus in intestinal microbiota is related to glycolipid metabolism ( Huang et al., 2023 ; Lahtinen et al., 2023 ), and Enterorhabdus abundance in PCOS mice is positively correlated with T level and blood glucose ( Li Y. et al., 2023 ). Interferon may affect the expression level of important metabolites in uterine tissue by reducing the abundance of Enterorhabdus in intestinal microbiota, thus alleviating the injury of endometritis in mice ( Xue et al., 2023 ). Lactobacillus has a protective effect on the ovaries, restoring luteinizing hormone, follicle-stimulating hormone, and testosterone levels, upregating short-chain fatty acid levels, and improving intestinal microbiota disorders ( He et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the level of genus, Muribaculum , Akkermansia, and Parasutterella are closely related to anti-inflammation, and a diminished level of Muribaculaceae is a critical contributor to colitis pathogenesis Eubacterium_xylanophilum_group , and Enterorhabdus act a pro-inflammatory role in the inflammation of gut. These results further confirmed that the alleviation of intestinal inflammation and the repair of the barrier by SAL were tightly linked to gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly used to study the molecular relationship between nutrients and biochemical processes, to analyze the effects of food nutrients on metabolism, and to study the cross-genomic metabolite interactions between mammalian hosts and gut microflora as depicted in Fig. 3 [149][150][151]. Metabolites in body fluids are usually influenced by endogenous and exogenous factors, endogenous factors such as gender, age, underlying diseases, etc.…”
Section: Nutrimetabonomicsmentioning
confidence: 99%